Comparative structural analysis of cytoplasmic and chloroplastic 5S rRNA from spinach. - Pieler, T (1983)
5S rRNAs from Spinacea oleracea cytoplasmic and chloroplastic ribosomes have been subjected to digestion with the single strand specific nuclease S1 and to chemical modification of cytidines by sodium bisulphite in order to probe the RNA structure. According to these data, cytoplasmic 5S rRNA can be folded as proposed in the general eukaryotic 5S rRNA structure (1) and 5S rRNA from chloroplastides is shown to be more related to the general eubacterial structure (2).